2008
DOI: 10.3174/ajnr.a1123
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Traumatic Injuries of the Vertebral Artery

Abstract: BACKGROUND AND PURPOSE:There are a few reports regarding the treatment of traumatic vertebral arteriovenous fistulas and pseudoaneurysms. Our aim was to describe the clinical and angiographic results of endovascular therapy for traumatic injuries of the vertebral artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
100
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 19 publications
(30 reference statements)
2
100
0
2
Order By: Relevance
“…Endovascular techniques such as coil embolization and stent placement have gained increasing popularity in the treatment of blunt vascular injuries including pseudoaneurysm, fistula, and flow-limiting dissections. While some studies have raised concerns over the safety of endovascular techniques as a result of increased risks of stroke and stent occlusion 17,27,34 , other groups have reported good longterm results with endovascular treatment [35][36][37][38] . Specifically, endovascular occlusion has been advocated as a feasible and safe treatment for traumatic vertebral arteriovenous fistula 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular techniques such as coil embolization and stent placement have gained increasing popularity in the treatment of blunt vascular injuries including pseudoaneurysm, fistula, and flow-limiting dissections. While some studies have raised concerns over the safety of endovascular techniques as a result of increased risks of stroke and stent occlusion 17,27,34 , other groups have reported good longterm results with endovascular treatment [35][36][37][38] . Specifically, endovascular occlusion has been advocated as a feasible and safe treatment for traumatic vertebral arteriovenous fistula 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…The disorder may result in vertebrobasilar ischemia, vertigo, diplopia and cephalgia due to arterial steal. Venous hypertension of dilated epidural veins caused by blood flow to spinal veins may result in root compression, pain and myelopathy (8,12). We showed an AVF at the left vertebral artery where the vertebrobasilar system could not filled via left catheterization, but filled with right catheterization via the right posterior communicating artery (steal phenomenon) in our case.…”
Section: Yilmaz Mb Et Al: Penetrating Vertebral Artery Injurymentioning
confidence: 70%
“…Traumatic fistulas are mostly seen at the second part of the artery where it courses within the foramen transversarium (26). Although most cases have been reported below the C5 level, Herrera et al have found the majority of traumatic fistulas between C2-5 in their series (12). This is due to the high incidence of traumatic cervical injuries at the C2-5 levels.…”
Section: Yilmaz Mb Et Al: Penetrating Vertebral Artery Injurymentioning
confidence: 91%
See 1 more Smart Citation
“…The sensitivity for detecting extracranial vertebral artery dissection was estimated around 75% in literature. Anyway the distal V2 and V3 segments cannot always be satisfactorily imaged; therefore, diagnosis is based on indirect hemodynamic signs [20][21][22][23]. Whereas angiography only shows an alteration of the vessel lumen, duplex color-flow imaging provides additional information about the hemodynamic parameters and the pathology of the vessel wall.…”
Section: Discussionmentioning
confidence: 99%